(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
Abstract This article examines the environmental and occupational safety aspects of technologies used to enhance the wear resistance of working surfaces in mill and pump components. The main risk factors related to abrasive materials, thermal treatments, coating applications, and the use of chemicals are identified, along with their impacts on the working environment and operator health. The advantages of modern eco-friendly surface strengthening methods, automated enclosed systems, and effective ventilation and filtration solutions are highlighted. Recommendations are provided for implementing safe and environmentally responsible technological regimes in industrial settings involving mill and pump component maintenance and manufacturing.